2022
DOI: 10.1002/vetr.1487
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review to assess online information available to new dog owners

Abstract: Background: Many dog owners turn to the internet for pet care advice. As internet resources can positively or negatively influence owners' decision making and thus impact dogs' welfare, the identification of trustworthy information online is crucial. Methods: A scoping review was conducted in 2014, and repeated in 2021, to assess the availability and quality indicators of information resources generated from Google searches using empirically derived dog owner internet search terms. Results: A total of 121 uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…38 Owners find it important to access reliable and correct online information, and feel the need for guidance by a veterinarian when looking for trustworthy information online. 36,39,40 Client-veterinarian communication is of paramount importance when CAVM therapies are used, especially since herbal supplementation was frequently reported in this study. Non-disclosure of self-administered supplements raises concerns regarding lack of product quality control, potential direct toxicity, interference with the pharmacokinetics of other drugs or unwanted drug interaction.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…38 Owners find it important to access reliable and correct online information, and feel the need for guidance by a veterinarian when looking for trustworthy information online. 36,39,40 Client-veterinarian communication is of paramount importance when CAVM therapies are used, especially since herbal supplementation was frequently reported in this study. Non-disclosure of self-administered supplements raises concerns regarding lack of product quality control, potential direct toxicity, interference with the pharmacokinetics of other drugs or unwanted drug interaction.…”
Section: Discussionmentioning
confidence: 90%
“…The internet is indicated as an important source of health information in the literature. 36 In a study of 1622 pet owners, 72.7% indicated that they used the internet for pet health information at least occasionally. 37 Social media, including Facebook groups, also plays an important role as a source of information, with many owners reporting it as a 'useful, but not entirely trustworthy' source.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, online step-by-step guides are available for adoption which could help dog lovers in adopting a village dog [ 43 , 44 ]. However, the lack of reliable indicators of quality in online information would be a barrier to dog owners’ access to reliable information [ 45 ] in addition to the lack of internet access in developing and rural regions.…”
Section: Discussionmentioning
confidence: 99%